Ganho genético para caracteres agronômicos de genótipos de feijão avaliados em Santa Maria entre 1998 e 2021 - Santos, Greice Godoy dos (2022)
In Brazil, the supply of beans is not always enough to meet consumer needs. As it is a culture of great importance to the national rotine of food, the use of cultivars with greater productive potential, early cycle and upright plant architecture are desired both by producers and by breeding programs. Therefore, evaluating the genetic gain obtained for these agronomic traits is necessary to analyze efficiency in launch of new common bean cultivars. Therefore, the objective of this study was to evaluate the genetic gain of grain yield and its components, as well as phenological and plant architecture traits applied to a database of Value of Cultivation and Use (VCU) experiments conducted from 1998 to 2021. All experiments were carried out in a randomized block design, with three or four replicates, in experimental area of the Federal University of Santa Maria, in rain and dry seasons. The treatments consisted of bean genotypes of different types of grains obtained by the Southern Brazilian Common Bean Network. The following traits were evaluated: grain yield, number of pods per plant, number of grains per pod, mass of 100 grains, flowering, cycle, lodging, general adaptation score, height of insertion of the first pod, and height of the last pod. The genetic gain was estimated by the Vencovksy methodology. The new common bean lines developed between 1998 and 2021 show desirable genetic gain for grain yield (1.50%), mass of 100 grains (2.15%), lodging (-3.64%), general adaptation score (-2.47%), and height of insertion of the first pod (4.83%). On the other hand, number of pods per plant (-5.83%), number of grains per pod (-0.45%), flowering (0.95%), cycle (0.29%), and height of insertion to the last pod (1.83%) did not correspond to the expectations of the breeding programs. Finally, common bean cultivars with high grain yield and upright plant architecture are being launched by breeding programs, meeting the demand of rural producers for efficiency in mechanized harvesting.